A Study on The Perceptions of Youths and Their parents on vocational and technical training — Sarawak / Yap Yin ... [et al.] - Yap, Yin; Mahdi, Rasidah; Song, Saw Imm (2000)
The objectives of this study are to obtain a profile of the socio —economic background of youths and their parents in Sarawak and their awareness and perceptions towards vocational and skills training. Based on the results of the analysis, recommendations are suggested to the State Government. A quota sample of 608 youths age between 15-30 and their parents reflective of the demographic and socio-economic profile of Sarawak is chosen. The findings show that 19.6 per cent of the youths are unemployed 38.7 per cent are employed, 38.5 per cent are schooling and 3.5 per cent are waiting to further studies.